'The Living Word Has Its Way with You': The Apocalyptic Homiletics of Rev. Fleming Rutledge. Issue 3 (1st September 2020) - Hartelius, E. Johanna; Micheli, Jason
ABSTRACT: This article examines the tandem functions of rhetoric and theology through a case study of the apocalyptic homiletics of Rev. Fleming Rutledge, one of the first women ordained to the Episcopal priesthood. We propose that apocalyptic rhetoric might be understood not only with reference to its topics (such as a cataclysmic end of days) or context (social disarray), but as a disclosive and revelatory announcement. Central to this disclosure is the homilist's orientation to agency and the etymology of apocalypsis from the Greek apokaluptein, to reveal by unveiling ( kalumna, veil). Through a reading of Rutledge's sermons (1978–2006), contrasting them with mainline Protestant preaching from the 1970s onward, we identify three qualities of apocalyptic homiletics: revelation, catechism, and a totalizing perspective. Offering a distinct theology of rhetoric, the article expands the field of apocalyptic rhetoric by approaching revelation as a theological and rhetorical disclosure-through-intervention, involving the rhetor with divine becoming and perfection.